Deep‐Red Phosphorescent Iridium(III) Complexes with Chromophoric N‐Heterocyclic Carbene Ligands: Design, Photophysical Properties, and DFT Calculations (Eur. J. Inorg. Chem. 11/2016). Issue 11 (April 2016) - Lanoë, Pierre‐Henri; Chan, Jonny; Gontard, Geoffrey; Monti, Filippo; Armaroli, Nicola; Barbieri, Andrea; Amouri, Hani
Abstract : The cover picture shows the drawing of an octahedral cyclometalated iridium complex containing an N‐heterocyclic carbene attached to a naphthalimide chromophore. The molecular structure of the complex is shown next to it. The compound is a deep‐red emitter, as illustrated by the color of the round‐bottomed flask containing the microcrystalline compound. The 1 MLCT absorption is represented by a blue arrow, while the red color represents the emission, which is mostly naphthalimide‐ligand‐centered ( 3 IL) and responsible for the observed deep‐red color with a long lifetime. The background shows a beautiful red sunset on the northwestern French coast of Brittany, captivating scenery to brighten our daily life. Details are discussed in the Communication by A. Barbieri, H. Amouri et al. onp. 1631 ff . For more on the story behind the cover research, see theCover Profile .